What is the importance of Scientific Congresses? Conceptions of postgraduate students and professors of Chemistry from a public university (Research, Society and Development, 2021)
Understanding what students and professors of Chemistry think about Science and scientific work, both in terms of diagnosis and reflections on the education of future scientists. A little explored discussion in the literature is the importance of Scientific Congresses for academic formation in the opinion of members of this community. A qualitative research was carried out, in which were analyzed the answers of a group of subjects (postgraduate studentes and professors) given to some questions: Do you usually go to scientific congresses? What is the importance of scientific congresses in scientific education?. The analysis was developed using the Discursive Textual Analysis and it was possible to conclude that the majority prefer to attend specific congresses of the field, and most of them participate at least once a year, mainly with the purpose of identifying themes there are commonly presents in the researches and interacr with others researchers.